Dynamic power sharing control among converter-interfaced DERs in an autonomous microgrid - Hosseinimehr, T.; Shahnia, Farhad; Ghosh, Arindam (2015)
This paper presents a new control approach to facilitate dynamic power sharing among parallel converter-interfaced distributed energy resources (DERs) in an islanded microgrid (MG). It is assumed that the power ratio is determined by the distribution network tertiary controller and passed to the primary controllers of each DER by the MG central controller. In this paper, an internal balancing inductance (IBI) is imposed to the system by the DER converter control which ensures the desired power ratio at the output of the DER converter and filter system. Stability analysis of the MG system is investigated with the proposed control approach. The proposed method defines the optimal IBI to guarantee the system stability and minimum error in the ratio of the output active and reactive power among the DERs. The discussions are validated for an islanded MG through PSCAD/EMTDC and MATLAB simulation studies.